Professional Endorsement of Teachers and its Influence on the Improvement of Learning Achievement of Students: Perspectives of Teachers - Rusli Ruslin (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC EDUCATION, 2019)
Teacher endorsement (well-known as teacher certification in Indonesian basic and secondary education) is essentially aimed to improve the quality of Indonesian education. In this context, the government of Indonesia has paid special attention to three required qualities of teachers: competences, work motivation, and their well-beings (The Law No. 14, 2005). Since the role of teachers is central to the improvement of learning achievement of students, this study discusses the concept of teacher endorsement, the views of teachers regarding professional endorsement in relation to different tasks of teachers, and its influences on the improvement of students’ learning achievement. The study uses qualitative approach where three types of data collections techniques are employed: document reviews, semi-structured interviews, and observations. The findings of the study show that professional teacher endorsement program had not yet fully supported the improvement of teachers’ professionalism as required by the Law No 14, 2005. Besides, the understanding of teachers about requirements for being professional was still underprivileged leading to poor learning achievement of their students. Therefore, the study informs the needs for educational stakeholders to provide continuous counselling, motivation, and guidance for teachers in order for them to take this matter into serious accounts which in the end would help the government of Indonesia achieve its educational goal.